Curar la carne para conjurar la muerte. Exhumación, segundo velorio y segundo entierro entre los wayuu: rituales y prácticas sociales (2009)
ABSTRACT: The paper analyzes the more important ritual manifestations related to death among the indigenous Wayuu. It describes in detail the first burial and its subsequent exhumation. As well, it discusses the manner in which the alimentary practices in these rituals express the beliefs about death at the same time that it reinforces and structures social relations.